2013
DOI: 10.5387/fms.59.15
|View full text |Cite
|
Sign up to set email alerts
|

HENOCH-SCH^|^Ouml;NLEIN PURPURA NEPHRITIS IN CHILDHOOD: PATHOGENESIS, PROGNOSTIC FACTORS AND TREATMENT

Abstract: : Henoch -Schönlein purpura (HSP) is a systemic disorder characterized by leukocytoclastic vasculitis involving the capillaries and the deposition of IgA immune complexes. Renal involvement is the principal cause of morbidity and mortality in children with HSP. Thus, it is important to clarify the onset mechanism as well as the prognostic factors of Henoch -Schönlein purpura nephritis (HSPN) and to identify the most appropriate treatment. We herein review the pathogenesis, the prognostic factors and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 46 publications
2
44
0
5
Order By: Relevance
“…Further, the capillary walls have varying degrees of involvement [14]. The present study showed immune complex depositions in NP group (mainly IgA immune deposits, followed by IgA + IgM immune deposits).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Further, the capillary walls have varying degrees of involvement [14]. The present study showed immune complex depositions in NP group (mainly IgA immune deposits, followed by IgA + IgM immune deposits).…”
Section: Discussionmentioning
confidence: 61%
“…In our study, the choice of treatment for HSPN depended on both the histological and clinical severity of the patient conditions [13, 14, 17]. All patients received ACE-I and/or ARB, and dipyridamole.…”
Section: Discussionmentioning
confidence: 99%
“…In HSP, renal involvement is the most important prognostic factor for the determination of morbidity and mortality and, in contrast to gastrointestinal and joint involvements, it may manifest as a delayed sequel [11][12][13][14]. Generally, the first urinary abnormality occurs after other symptoms [15]. Microscopic hematuria, with or without proteinuria, is the most common renal symptom [15].…”
Section: Discussionmentioning
confidence: 99%
“…Hastalık başlangıcında inatçı döküntü ve şiddetli karın ağrısı görülen olgularda böbrek tutulumu daha sıktır. Böbrek tutulumu geçici izole mikroskopik hematüriden hızlı ilerleyen glomerülonefrite kadar değişen klinik spektrumda karşımıza çıkabilir (11). Hematüri nefritli olguların tamamında görülürken, proteinüri, nefrotik sendrom, HT ve ABY daha az sıklıkta…”
Section: Discussionunclassified